Improving Financial Management in Sub-Saharan Africa - Johnson, Sonia R. (World Bank, Washington, DC, 2012)
This paper describes the status of accounting and auditing in sub-Saharan Africa (SSA), and the importance of having an auditing profession which is seen to maintain the highest standards. The paper assesses existing schemes for reviewing the quality of the work of auditors, describes the results of two pilot tests in Tanzania and Senegal, and recommends that similar schemes be introduced in SSA as a way to maintain standards.